Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 48; b = -13 ;c = -1


= 48× - 1 = - 48


And either of their sum or difference = b


= - 13


Thus the two terms are - 16 and 3


Difference = - 16 + 3 = - 13


Product = - 16.3 = - 48




16x(3x-1) + 1(3x-1) = 0


(16x + 1)(3x-1) = 0


(16x + 1) = 0 or (3x-1) = 0


x = (-1)/6 or x = 1/3


Roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics